2019
DOI: 10.1007/s42729-019-00139-3
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Selenium-Instigated Physiochemical Transformations Impart Terminal Heat Tolerance in Bt Cotton

Abstract: High temperature during reproductive stages of cotton is a major constraint to achieve potential yield of cotton. The aim of the present study was to determine comparative thermo-sensitivity of squaring and flowering, to optimize exogenous selenium for heat-stressed cotton, and to explore correlation among physiochemical and morphological attributes. The experiment was conducted during 2013 and repeated during 2014. The experiment was laid out in randomized complete block design under split plot arrangement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In this study, we showed that the DS enhanced the APX, SOD, POD and CAT antioxidant enzymes in the strawberry leaves, which was identical with the results of previous studies in other plants. Some studies have shown that inorganic Se relieved oxidative damage in plants through antioxidant enzymes under many stresses, such as salt, drought, heat and cadmium stresses (Sattar et al 2019;Saleem et al 2020;Sharifi et al 2021;Xie et al 2021). For drought Compared with inorganic Se, our findings showed that SeMet had something in common with regulating the APX, SOD and CAT activities in strawberry plants.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In this study, we showed that the DS enhanced the APX, SOD, POD and CAT antioxidant enzymes in the strawberry leaves, which was identical with the results of previous studies in other plants. Some studies have shown that inorganic Se relieved oxidative damage in plants through antioxidant enzymes under many stresses, such as salt, drought, heat and cadmium stresses (Sattar et al 2019;Saleem et al 2020;Sharifi et al 2021;Xie et al 2021). For drought Compared with inorganic Se, our findings showed that SeMet had something in common with regulating the APX, SOD and CAT activities in strawberry plants.…”
Section: Discussionmentioning
confidence: 61%
“…During the whole experiment, we used an 0.01 g electronic balance (HZY-B6000 Xinling, China) to weigh and then add water into Sharma 2021; Xie et al 2021). Meanwhile, many studies have shown that Se played an important role in fighting against stresses, including salt, drought, heat and cadmium stresses (Sattar et al 2019;Saleem et al 2020;Sharifi et al 2021;Xie et al 2021). It has been documented that DS induced the overproduction of reactive oxygen species (ROS), which caused peroxidation injuries to the plants (Bashir et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant role of Se in plants has been reported previously (Seppanen et al 2003;Saleem et al 2020). MDA is a key product of membrane lipid peroxidation, reflecting the degree of damage to plant cells (Kapoor and Singh 2017).…”
Section: Effects Of Se Supplementation On Antioxidant Capacity and Gsmentioning
confidence: 93%
“…Thus, Pn activity and fluorescence were reduced when the temperature was above 35°C due to temperature dependency (Gonias et al 2008). It might be because of the fact that the sensitivity of Pn to high temperature was due to the damage of Photosystem-II (PS-II) components in the chloroplast as well as membrane properties (Du et al 2019;Saleem et al 2020). They further claimed that Pn appeared to be higher because of reduced photorespiration in MCtreated plants.…”
Section: Physiological Aspects Of Mepiquat Chloride Application In Comentioning
confidence: 99%